Upaya Mahasiswa Kampus Mengajar Dalam Mengatasi Kesulitan Belajar Membaca Pada Siswa SDN Sumbersalak 02 - Wheka Isnanda; Astri Widyaruli Anggraeni (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
The author's background in taking this problem is because reading ability is one of the most important parts of the learning process in continuing students' academic levels in the future. This research shows the following results (1) Students in grades 4, 5, and 6 have different reading learning abilities in each class. (2) The teaching and learning process for students in grades 4, 5, and 6 who have difficulty learning to read differs depending on the teaching method and the actions taken by the teacher in the classroom. (3) Supporting and inhibiting factors for students at teaching campus 6 in overcoming difficulties in learning to read for students in grades 4, 5 and 6 at SDN Sumbersalak 02. The problems that students have are also different and the same among other students. (4) Efforts for students to teach. 6 to overcome students' difficulties in learning to read.